2013
DOI: 10.3389/fimmu.2013.00311
|View full text |Cite
|
Sign up to set email alerts
|

Location, Location, Location: The Impact of Migratory Heterogeneity on T Cell Function

Abstract: T cell migration is crucial for an effective adaptive immune response to invading pathogens. Naive and memory T cells encounter pathogen antigens, become activated, and differentiate into effector cells in secondary lymphoid tissues, and then migrate to the site(s) of infection where they exert effector activities that control and eliminate pathogens. To achieve activation, efficient effector function, and good memory formation, T cells must traffic between lymphoid and non-lymphoid tissues within the body. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 121 publications
(117 reference statements)
2
32
0
Order By: Relevance
“…CD103 and VLA-1 expression has been defined as a residential surface marker for the T-cells in nonlymphoid tissues [18][19][20]. Currently, homing molecules involved in migration of antigen-experienced T-cells to the lung are not well established [21]. This is partly due to the lack of techniques to discriminate intravascular and tissue residing T-cells in the past.…”
Section: Protection Against Pulmonary Tb Is Determined By the Differementioning
confidence: 91%
See 1 more Smart Citation
“…CD103 and VLA-1 expression has been defined as a residential surface marker for the T-cells in nonlymphoid tissues [18][19][20]. Currently, homing molecules involved in migration of antigen-experienced T-cells to the lung are not well established [21]. This is partly due to the lack of techniques to discriminate intravascular and tissue residing T-cells in the past.…”
Section: Protection Against Pulmonary Tb Is Determined By the Differementioning
confidence: 91%
“…Following immunisation, local dendritic cell populations acquire antigens and subsequently migrate to the local draining lymph node, priming and activating naïve T-cells. It has been suggested that such antigen-presenting cells play an important role in influencing the expression of receptors critical to the migration of T-cells (termed migratory receptors) to specific tissue sites (reviewed by BAATEN et al [21]). …”
Section: Effect Of Local Pro-inflammatory Signals On the Distributionmentioning
confidence: 99%
“…However, these signals are not entirely clear. The molecules that mediate the interaction between leukocytes and blood wall endothelia have been documented(24). CD44, integrins, selectin ligands and inflammatory chemokine receptors on activated T cells cooperate to mediate the engagement with endothelia.…”
Section: Introductionmentioning
confidence: 99%
“…T-lymphocytes use integrins to migrate in and out of lymph nodes and, following infection, to migrate into other tissues(14, 17, 18, 25). Integrins are key to the immunological cross-talk between T cells and antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…They are responsible for efficient migration of, among other cells, lymphocytes from the lymph nodes to the site of wound or infection(17, 18). Among the integrins expressed upon T-Lymphocytes, Integrin β1 and β2 are involved in lymphocyte functions, such as mediating T-cell interactions with other cells as well as modulating intra-cellular signaling.…”
Section: Introductionmentioning
confidence: 99%